Prevalence and Risk Factors of Latent Tuberculosis Infection (LTBI) at Madura Boarding School as a High-Risk Congregate Setting - Ananto, Muhammad Arif; Setyoningrum, Retno Asih; Lestari, Pudji (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2024)
Highlights: Boarding school is a high-risk location for tuberculosis transmission. Therefore, stricter early prevention measures are required. Gender and knowledge level were significantly related to latent tuberculosis infection, but there was no significant relationship between age and nutritional status. Low level of knowledge was the highest risk factor compared to other factors, with a five times greater risk of contracting latent tuberculosis infection.   Abstract Introduction: Tuberculosis (TB), caused by Mycobacterium tuberculosis (MTB), is a highly contagious airborne disease. High-risk environments with frequent close interactions contribute to the spread of TB. This study examined latent TB infection (LTBI) epidemiology in such settings to inform public health interventions and strategies to curb TB transmission in similar environments. Methods: This cross-sectional observational study, conducted from January to August 2022 at two boarding schools in Bangkalan, involved 100 adolescents aged 10-18 years old tested for latent tuberculosis infection using interferon-gamma (IFN-γ) release assay (IGRA). Data were collected via questionnaires. Bivariate analysis was used to determine the correlation between latent tuberculosis infection prevalence and each research variable using Pearson Correlation and odds ratio (OR) to find risk factors for each variable. A p<0.05 was considered statistically significant. Results: This study found that 30% of 100 adolescents in boarding schools had latent tuberculosis infection. Risk analysis showed a significant association between gender and LTBI (p=0.000), with males having a higher risk with an odds ratio (OR) of 1.02 times. Additionally, lower education levels were significantly associated with a higher risk of LTBI (p=0.021) with an odds ratio of 5.2 times. Conclusion: Boarding schools pose a tuberculosis transmission risk. Early latent tuberculosis infection screening is essential for tuberculosis eradication in Indonesia, and these findings emphasize the need to improve latent tuberculosis infection detection and prophylaxis therapy as a preventive measure against tuberculosis outbreaks.